"Tradition, rationality, and change: Essays in sociology of economic development and social change" - Rao, M.S.A (Bombay Popular Prakashan, 1972)
The problems of economic growth especially in the tradition-bound underdeveloped countries need examination from different angles. In the growing dynamic relationship between economic development and social change the traditional social structure produces its own inbuilt reactions and at the same time the consequences of economic development influence the changes in social structure. These are the two themes underlying the essays in this volume. Prof. M. S. A. Rao analyses the sociological aspects of the economic development followed in the wake of community development programmers to reveal its impact on the institutions of caste, on the efforts made to achieve egalitarian society and to reduce the gap between the rich and the poor. the sense of commitment on the part of Indian labour in the industrial develop- He also discusses Iment and the relation between Hindu religion and economic development. While dealing with the theme of social change, the author covers a wide range of areas of social life such as caste, religion, politics, foamily organization and social stratifications. He discusses the influence of caste and the growth of communalism in the modern process of politicization and the changes that have occurred in the traditional family organization as a result of occupational differentiation and commercialization, changes in inter- caste relations and religious reforms.